Investigating the Lexicon in Cognitive Semantics: Opportunities and Prospects - Kurbanbaev, Djavod (The Lingua Spectrum, 2025)
The article outlines how cognitive linguistics can be used to investigate the lexicon by foregrounding its core principles and a multi-layered view of the concept as category, unit and structure with a perceptual – cognitive – affective nature. It presents linguistic categorization via macro-, micro- and subcategories (substantial, attributive, relational), highlights the mismatch between real and conceptual worlds, and shows the role of language in mapping between them. Within an anthropocentric paradigm, the study examines paremiological units, discussing idiomaticity, motivation, connotation, functional variants and sociolinguistic tagging, together with criteria for selecting and representing proverbs in lexicography. In dialogue with traditional linguistic semantics, the paper revisits the principles of repetition, reduction, semantic fields, isomorphism and the core–periphery distinction. It concludes by clarifying the content – form relation and by showing how concepts structure knowledge about entities, properties and relations in the material world, informing practical dictionary-making.